A Modification of the Stapled TransAnal Rectal Resection (STARR) Procedure for Rectal Prolapse. (December 2018) - Lin, Hong-Cheng; Chen, Hua-Xian; He, Qiu-Lan; Huang, Liang; Zhang, Zheng-Guo; Ren, Dong-Lin
Purpose . This study was designed to assess the safety, efficacy, and postoperative outcomes of the modified Stapled TransAnal Rectal Resection (modified STARR) in patients presenting with cases of limited external rectal prolapse. Methods . A prospective cohort of patients with mild rectal prolapse undergoing rectal resection with the Tissue-Selecting Technique Stapled TransAnal Rectal Resection Plus (TSTStarr Plus) stapler between February 2014 and September 2016 was reviewed retrospectively. Results . Twenty-five eligible patients underwent rectal resection with the TSTStarr Plus stapler. The median vertical height of the resected specimen was 5.0 cm (range = 3.1-10 cm) with all cases being confirmed histologically as full-thickness resections. Over a follow-up of 33.6 ± 9.4 months, only 1 case (4%) was encountered with recurrence. The mean postoperative Wexner score was significantly improved when compared with the preoperative scores (preoperative: median = 3, range = 0-20, vs postoperative: median = 2, range = 0-20, respectively; P = .010). The median preoperative Symptom Severity Score and Obstructed Defecation Score were both decreased compared with the postoperative scores ( P = .001). Conclusions . Modified STARR in management of mild rectal prolapse appear to be a safe and effective technique. The initial results would encourage a more formal prospective assessment of this technique as part of a randomized trial for the management of mild rectal prolapse.